A Novel Harmonic Suppression Antenna with Both Compact Size and Wide Bandwidth - Zhou, Zhi-Li; Li, Li; Hong, Jing-Song; Wang , Bing-Zhong (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A novel CPW-fed harmonic suppression antenna with both compact size and wide bandwidth is proposed and investigated in this paper. The second and third harmonic frequencies are suppressed effectively with square-shaped lattices inserted in the ground plane. Furthermore, by exploiting the Vivaldishaped structure and two simple rectangular slots, wide bandwidth (1.86GHz) ranging from 1.9GHz to 3.76GHz is also obtained with rather compact size of 10mm × 10mm, which is much smaller than that have ever been reported before. Eventually, the measured results confirmed the simulated dates.